Preventive Curative Inheritance Governance among Urban Muslim Families: Evidence from Depok, Indonesia - Ahmad Rifai; Agus Mahmud; Gazi Saloom; Amirfajar Masae; Azis Faturokhman (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Inheritance conflicts in Muslim families are not only related to the distribution of inheritance, but are also socio-juridical and economic issues that are influenced by kinship relationships, asset documentation, economic value of property, and compliance with religious norms. This study aims to analyze inheritance governance in urban Muslim families in Depok, Indonesia, as well as develop a governance model that is able to prevent and resolve inheritance conflicts in a sustainable manner. The study used a socio-juridical qualitative approach with data obtained through semi-structured interviews with 18 informants, analysis of Religious Court decisions, legal documents, and official demographic data. Analysis is carried out through open, axial, and selective coding, while the validity of findings is guaranteed through source triangulation, member checking, peer discussion, and trail audit. The results of the study show that the effectiveness of inheritance governance is determined by the interaction between legal literacy, economic rationality, and family communication. Legal literacy allows for proper distinctions between grants, wills, common property, inheritance, debts, and heirs' rights, while economic rationality influences inherited asset management decisions. Open communication, supported by asset documentation, grants, written wills, and family deliberations, has been proven to strengthen conflict prevention. On the other hand, when preventive mechanisms do not work, dispute resolution develops gradually through family negotiations, religious consultations, community mediation, legal assistance, and adjudication in Religious Courts. This research offers a Preventive-Curative Inheritance Governance Model that integrates legal literacy, economic rationality, family communication, legal pluralism, and institutional settlement stages as conceptual contributions to the development of Muslim family inheritance governance in Indonesia.